Computed tomographic features of exocrine pancreatic carcinomas in dogs and cats - Dunn, Alexandra; Rao, Sangeeta; Husbands, Brian; Petrovitch, Nicholas; Loeber, Samantha; Schwarz, Tobias; Cline, Kelsey; Mai, Wilfried; Spain, Heather; Curran, Kaitlin; Vickery, Kate; Marolf, Angela (Veterinary radiology & ultrasound, 2024)
Exocrine pancreatic carcinomas are uncommon in dogs and cats, and diagnosis with diagnostic imaging can be challenging. This retrospective, multi‐institutional, descriptive study was performed to evaluate the CT features of exocrine pancreatic carcinomas. The CT examinations of 18 dogs and 12 cats with exocrine pancreatic carcinomas diagnosed by cytology or histopathology were reviewed. The CT features of exocrine pancreatic carcinomas included a well‐defined mass in 28/30 (93%) with contrast enhancement in 27/30 (90%), commonly heterogeneous 22/30 (73%); often with a nonenhancing fluid to soft tissue attenuating center 12/30 (40%). The right lobe of the pancreas was the most common location, 14/30 (47%), then the left lobe, 10/30 (33%), and the body, 6/30 (20%). Extrahepatic biliary duct dilation was present in six animals; 5/6 (83%) of the masses were located in the right pancreatic lobe. Additional findings included peripancreatic fat‐stranding 17/30 (57%), lymphadenopathy 16/30 (57%), peripancreatic soft tissue nodules 12/30 (40%), and free fluid 10/30 (33%). When comparing the imaging features of dogs and cats, there was a large overlap in imaging characteristics. There was a significant difference between the height of the masses, with dogs having larger masses (P‐value.0028). Lymphadenopathy was more likely in larger masses [increased height (P‐value.029)]. Cats were significantly older than dogs (P‐value.0355). Pancreatic carcinomas were commonly identified as masses with heterogeneous contrast enhancement and a nonenhancing fluid to soft tissue attenuating center with concurrent peripancreatic changes (fat‐stranding and/or soft tissue nodules) and lymphadenopathy.